2022
DOI: 10.1186/s12883-022-02996-5
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of tirofiban on stroke outcome after mechanical thrombectomy in acute vertebrobasilar artery occlusion

Abstract: Background Even undergoing mechanical thrombectomy (MT), patients with acute vertebrobasilar artery occlusion (AVBAO) still have a high rate of mortality. Tirofiban is a novel antiplatelet agent which is now widely empirically used in acute ischemic stroke (AIS). In this study, we aimed to evaluate the safety and efficacy of tirofiban as adjunctive therapy for MT in AVBAO. Methods From October 2016 to July 2021, consecutive AVBAO patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…6). Sensitivity analysis showed that after the removal of the Pan et al [27] study, the I 2 value decreased to 0, suggesting a major source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6). Sensitivity analysis showed that after the removal of the Pan et al [27] study, the I 2 value decreased to 0, suggesting a major source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Third, previous studies have suggested that tirofiban has a better safety profile and lower risk of hemorrhage in patients with large atherosclerotic stroke compared with cardiogenic stroke. In 2 clinical studies of the posterior circulation, Chen et al [26] and Pan et al, [27] the tirofiban group had a significantly higher proportion of large artery atherosclerotic strokes. This was also the reason for the significantly lower rate of sICH in the tirofiban group in the posterior circulation subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach would enable the identification of patients who are more likely to experience bleeding complications and facilitate the implementation of appropriate risk mitigation strategies. However, studies by X. Pan et al and Y. Wang et al provide conflicting results regarding the safety of tirofiban in endovascular stroke treatment [ 12 , 22 ]. X. Pan et al evaluated the safety and efficacy of tirofiban as adjunctive therapy in patients with acute vertebrobasilar artery occlusion undergoing mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error to author Jie Yang’s affiliation. Affiliation 5 was removed for author Jie Yang.…”
mentioning
confidence: 99%